Utilisation of Technology Media for Effective Management of Prospective Workforce in Enhancing Digital Marketing Skills - Syahrul Ramadhan, Muhammad; Wulan Purnamasari; Wahyudi (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2024)
As digital technology continues to evolve, digital marketing skills are becoming a very important skill for prospective workers. Managing and developing these skills requires an efficient and effective approach, one of which is through the utilisation of technological media. This research aims to analyse the use of technological media in the management of workforce candidates to improve digital marketing skills effectively. The method used in this research is a literature study and survey of various technology platforms used in training and developing digital marketing skills. This research identified various types of technology media that can be used to support the training process, such as e-learning platforms, webinars, mobile applications, and social media. In addition, it explores the relationship between the utilisation of technology media and the improvement of workforce candidates' skills in key aspects of digital marketing, such as SEO, social media marketing, paid advertising and web analytics. The results show that the utilisation of technological media can improve the effectiveness of training management for prospective workers, enabling them to acquire digital marketing skills that are relevant to industry needs. In addition, the technology-based approach also provides greater flexibility and accessibility, facilitating more interactive and practice-based learning. Thus, proper utilisation of technological media can be key in preparing job candidates to face the challenges and dynamics of an increasingly competitive digital marketing industry.